Assessment of Growth Hormone , Insulin and Vit.D2 Levels for Children Suffering from Hypoweight in Kirkuk City - Nuha K. Ibrahim; Sahib J. Abdulrahman (Tikrit Journal of Pure Science)
This study was done in the Pediatric General Hospital and Al-azadi Educational Hospital , the period from September 2017 to February 2018, aimed to evaluate levels of Growth hormone (GH), Insulin and Vit.D3 levels for children suffering from hypoweight aged (1-5)years, include 40 child, in addition to 20 healthy child. A medical syringe was used for collecting blood samples, drawing (5)ml of venues blood from them and put it in test tube free from any coagulation material, it was put in centrifuge (3000rpm, 15min) for purpose obtaining blood serum then serum are separate and drawn by micropipette put it in a test tube used for (Growth Hormone, Insulin and Vit.D) tests. After test complete, the results of study showed a significant decrease (p≤ 0.01) in GH, Insulin and Vit.D2 levels.